The advantage of sleeve lobectomy over pneumonectomy - Maurizi, Giulio; Ciccone, Anna Maria; Rendina, Erino Angelo (Journal of Thoracic Disease, 2019)
The comment from Dr. Ludwig (1) to ore recent paper on lower sleeve lobectomy, the so-called “Y” sleeve (2), is interesting and it deals on some important points related to technical aspects in this setting. It is a pleasure to reply to an author that has published important contributions on sleeve lobectomy, reporting, over time, results from patients that had undergone sleeve lobectomy and pneumonectomy.